The Challenges of President Muhammadu Buhari’s (PMB) Cash Nigeria Transfers as Poverty Reduction Strategy in Nigeria - Osondu-Oti, Adaora (Journal of Contemporary International Relations and Diplomacy, 2024)
Poverty has been on the increase in Nigeria. In 2016, the Federal government of Nigeria under President Muhammadu Buhari (PMB) established the National Social Investment Programs (NSIPs), including Cash Transfers (CTs). The cash transfers programme targeted the poorest of the poor by giving eligible households N5000 monthly (transferred bi-monthly), with the aim of graduating them out of poverty after three years of implementation. This paper analyzed the challenges that impeded the successful implementation of the PMB cash transfers. Using qualitative case-study methods, six Nigerian States were studied. Findings revealed that the program encountered several challenges such as poor targeting, inconsistent and incomplete payments, inadequate monitoring, bribery among other issues that resulted in its failure to lift the “poor beneficiaries” permanently out of poverty. For any future cash transfers to make positive impacts, it is recommended that Nigeria’s policymakers ensure that the challenges identified in this paper are adequately addressed.